Theoretical analysis of mixed open-circuit potential for high temperature electrochemical cells electrodes - Cammarata, A.; Mastropasqua, L. (Frontiers in Energy Research, 2023)
The Nernst equilibrium potential calculates the theoretical OCV, which estimates the best performance achievable by an electrochemical cell. When multiple semi-reactions (or multiple ionic species) are active in one of the electrodes, the calculation of the theoretical OCV is not straightforward, since different Nernst potentials are associated to each semi-reaction. In this paper, analytical equations for calculation of the theoretical OCV are developed, using the mixed potential theory. The case of H2 and CO co-oxidation (or H2O and CO2 co-reduction) in solid oxide cells is used as a reference case, but similar conclusions can be drawn for other equivalent cases. OCV data from literature are used to calibrate and validate the model. The relative reaction rate of H2 and CO semi-reactions is estimated within the calibration process, and the result is in line with assumptions and suggestions given by other authors. The validation procedure shows predicted OCV values in line with experimental literature data, except for mixtures with relatively large CH4 concentration (e.g., 8%), for which the OCV is significantly underestimated. This is expected when thermochemical reactions, in parallel to electrochemical reactions occur, since the additional H2 produced by internal steam methane reforming is not accounted within the local mixed potential model. A fuel cell polarization model is developed based on the results from the calibration procedure, and it is used to predict the polarization behavior of an SOFC fed with a H2-H2O-CO-CO2 fuel mixture. It is found that either H2 or CO may be reduced rather than oxidized via an equivalent electrochemical water-gas-shift reaction.